Income Diversification on Stability in Banking Industry A Systematic Literature Review - Handy OCTAVIANUS; Khaira Amalia FACHRUDIN (International Journal of Environmental, Sustainability, and Social Science, 2022)
This study aims to provide a deeper understanding of income diversification carried out by banks and provide guidelines for future researchers in conducting research related to the relationship between income diversification and bank stability. The method used in this research is the Systematic Literature Review (SLR), which identifies and assesses the findings of previous studies in order to guide further research in the future. There was 1 article from conference papers and 1 article from working papers. The remaining 28 articles came from well-known publishers. So 30 articles were obtained from well-known publishers and content following the topic of this literature review. The findings of this study indicate that the main motives for implementing the income diversification strategy are increased performance, reduced risk and competition between banks. This study also shows that there is a fairly wide research gap regarding the relationship between income diversification and bank stability. In addition, it was found that the Herfindahl Hirschman Index (HHI) is the most widely used measurement as a proxy for income diversification, and the generalized method of moment (GMM) is the most commonly applied statistical testing tool. The findings of this study are expected to provide a comprehensive picture of the implementation of the income diversification strategy and provide guidance for future research areas.